2017
DOI: 10.1111/ped.13344
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology in pediatric bone marrow transplantation survivors and their mothers

Abstract: Bone marrow transplantation is a significant stressor, especially for mothers. Clinicians should address the child and family as a whole in assessments and be aware of psychiatric symptoms in mothers and children who have had such a life-threatening condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…TA B L E 1 Baseline (perioperative) characteristics of pediatric transplant patients symptoms, indicating a high risk for PTSD. The prevalence of PTSS in the current study is similar to reports in pediatric bone marrow transplant recipients, 28 pediatric cancer survivors, 29 and a sample of adolescent heart, kidney, and liver recipients (in which 16.3% of the sample met all symptom criteria for PTSD). 11 However, tools other than the CTSQ were employed in the above studies to measure the prevalence of PTSS.…”
Section: Discussionsupporting
confidence: 82%
“…TA B L E 1 Baseline (perioperative) characteristics of pediatric transplant patients symptoms, indicating a high risk for PTSD. The prevalence of PTSS in the current study is similar to reports in pediatric bone marrow transplant recipients, 28 pediatric cancer survivors, 29 and a sample of adolescent heart, kidney, and liver recipients (in which 16.3% of the sample met all symptom criteria for PTSD). 11 However, tools other than the CTSQ were employed in the above studies to measure the prevalence of PTSS.…”
Section: Discussionsupporting
confidence: 82%
“…This research used the K-SADS-PL and reported that the incidence of anxiety disorder was significantly higher for transplant children compared with healthy peers. 31 A study by Zanato et al reported that children undergoing BMT had more attention problems compared with healthy peers. 32 Although ADHD is a well-known neurodevelopmental disease, Nylander et al reported that the ADHD rate was higher in adolescents with chronic illness than in healthy adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is one study that used a semi‐structured interview for children undergoing BMT. This research used the K‐SADS‐PL and reported that the incidence of anxiety disorder was significantly higher for transplant children compared with healthy peers . A study by Zanato et al reported that children undergoing BMT had more attention problems compared with healthy peers .…”
Section: Discussionmentioning
confidence: 98%